Pengaruh Metode Pembelajaran Berbasis Masalah Terhadap Self-Efficacy dan Kemampuan Pemecahan Masalah Matematis Ditinjau dari Kemampuan Awal Matematika Siswa SMA - Berliance Zamira Zebua; Francius Sipayung; Heldon Sihombing; Yunus Laia; Hardi Tambunan (Journal on Education, 2025)
This study aims to investigate the ability of self-efficacy and improvement of students' mathematical problem-solving ability through learning by using PBL methods. This study uses quasi experimental methods with final test control design for mathematical self-efficacy and pre-test posttest for mathematical problem-solving ability in terms of students' early math skills. The sample of this research is the students of class X in SMAS Pembda 1 Gunungsitoli and SMAS Pembda 2 Gunungsitoli in odd semester of academic year 2024/2025 as many as 96 students. The result of this researh are (1) There is an improvement of mathematical problem-solving ability of students who are treated with PBL methods is better than students who get conventional learning; (2) There is an interaction between learning method and early math ability (KAM) to improving students mathematical problem-solving ability; (3) There is an improvement of mathematical problem-solving ability in students with high KAM; (4) There is no improvement of mathematical problem-solving ability in students with low KAM; (5) self-efficacy of students who are treated with PBL methods is better than students who get conventional learning; (6) There is an interaction between learning method and early math ability (KAM) to self-efficacy of students; (7) There is different self-efficacy in students with high KAM; (8) There is no different of self-efficacy in students with low KAM.